Autonomy, self-governance and conflict resolution : innovative approaches to institutional design in divided societies - Weller, M. (Marc); Wolff, Stefan, 1969- (Routledge advances in international relations and global politics, 2005)
This book focuses on the resolution of self-determined conflicts, in which self-defined population groups fight to determine their own destiny within the boundaries of existing states.